2021
DOI: 10.1186/s12887-021-02646-8
|View full text |Cite
|
Sign up to set email alerts
|

Common diagnoses among pediatric attendances at emergency departments

Abstract: Background Pediatric patients present to Emergency Departments (EDs) with a variety of medical conditions. An appreciation of the common presenting conditions can aid EDs in the provision of pediatric emergency care. In this study, we established the common pediatric diagnoses seen at the general EDs, with reference to a pediatric ED. Methods A retrospective review of medical records was performed for patients less than 16 years old at a pediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Similar results were found by Mataloni et al [ 35 ], who reported a decrease of 50% in children up to the age of five years. The most common diagnoses in pediatric EDs are breathing difficulties, febrile illnesses, and gastroenterits [ 39 ], which mostly affect young children [ 40 ]. These diseases declined during and after the nationwide installation of NPIs [ 38 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found by Mataloni et al [ 35 ], who reported a decrease of 50% in children up to the age of five years. The most common diagnoses in pediatric EDs are breathing difficulties, febrile illnesses, and gastroenterits [ 39 ], which mostly affect young children [ 40 ]. These diseases declined during and after the nationwide installation of NPIs [ 38 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among critically ill patients, seizures, bronchiolitis, and asthma account for the most common diagnoses in pediatric EDs [ 40 ]. Since detailed analyses of diagnoses were not possible for the Italian and French speaking part of Switzerland due to unavailable data, changes in the diagnoses of ED patients in Zurich were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Fever is one of the most common concerns which results in presentation to the Emergency Department for children and their parents. 1,2 Caregiver anxiety regarding fever is high, despite the vast majority of fevers representing a benign self-limiting illness. [3][4][5][6] This can cause more frequent and urgent seeking of medical advice than is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Given that multiple studies have reported differences in CRS by sex and that ARS is such a common finding in pediatric patients, there is clinical utility in identifying the relationship of sex with the management of ARS in pediatric patients. [1][2][3][4][20][21][22][23][24][25][26][27] The objective of this study is to highlight the age-stratified impact of sex on the management of ARS in pediatric patients through a retrospective analysis of a large national inpatient pediatric database: the Kids' Inpatient Database (KID).…”
mentioning
confidence: 99%
“…A cute rhinosinusitis (ARS) is a possible sequela in 5% to 10% of cases of viral upper respiratory infections, with the latter being the most common cause for doctor visits in pediatric patients. [1][2][3][4] ARS typically occurs from a bacterial superinfection following a viral infection and is characterized by symptomatic inflammation of the paranasal sinuses and nasal cavity lasting \4 weeks. [5][6][7][8] Common symptoms include nasal congestion, purulent rhinorrhea, and facial pain.…”
mentioning
confidence: 99%